A new genus and two new species of phylinae (Heteroptera: Miridae) from the Andean-Patagonian region of Argentina - Carpintero, Diego L.; Chérot, Frédéric; Henry, Thomas J. (Zootaxa, 2023)
As a contribution to the Festschrift devoted to Dr. Aleksander Herczek, Adesmiaphylus n. gen., a new Phylini (Miridae: Phylinae) from the Andean-Patagonian region of Argentina, is described to accommodate two new species: A. manzanoensis, n. sp. from Neuquén Province and A. herczeki, n. sp. from Mendoza Province. Both species were collected on plants in the genus Adesmia DC. (Fabaceae).